2021
DOI: 10.3389/fnsys.2020.600582
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Homocysteine in Acute Ischemic Stroke Patients: A Systematic Review and Meta-Analysis

Abstract: Background: This comprehensive meta-analysis aimed to assess whether an increased homocysteine (Hcy) level is an independent predictor of unfavorable outcomes in acute ischemic stroke (AIS) patients.Methods: A comprehensive literature search was conducted up to August 1, 2020 to collect studies reporting Hcy levels in AIS patients. We analyzed all the data using Review Manager 5.3 software.Results: Seventeen studies with 15,636 AIS patients were selected for evaluation. A higher Hcy level was associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The meta-analysis of Huang et al (2020) investigated the prognostic utility of Hcy in individuals with acute ischemic stroke (AIS) in terms of all-cause mortality, poor functional outcome, and recurrent stroke. Independently elevated Hcy levels were linked with an increased risk of all-cause mortality but not poor functional outcome and recurrent stroke in subjects with AIS [91]. Another study revealed a causal association between plasma Hcy levels and ischemic stroke (IS) induced by small artery occlusion.…”
Section: Hhcy-associated Ischemic Strokementioning
confidence: 99%
See 2 more Smart Citations
“…The meta-analysis of Huang et al (2020) investigated the prognostic utility of Hcy in individuals with acute ischemic stroke (AIS) in terms of all-cause mortality, poor functional outcome, and recurrent stroke. Independently elevated Hcy levels were linked with an increased risk of all-cause mortality but not poor functional outcome and recurrent stroke in subjects with AIS [91]. Another study revealed a causal association between plasma Hcy levels and ischemic stroke (IS) induced by small artery occlusion.…”
Section: Hhcy-associated Ischemic Strokementioning
confidence: 99%
“…Hcy levels were significantly lower in the healthy control patients than in the AIS group with an SMD of 5.11 and 95% CI (1.87-8.35). Significant links between higher Hcy levels and the subject's survival were observed only in Caucasians and Asians [91]. In a meta-analysis of prospective cohort studies, Wu et al ( 2020) assessed the quantitative dose-response link of plasma Hcy levels with IS and stroke.…”
Section: Hhcy-associated Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…BA for females, but not for males. Previous researches had shown that the prevalence of hypertension and tHcy level were higher in males than in females (Doumas et al, 2013;Huang et al, 2021), the associations between hypertension, tHcy, cardiovascular and cerebrovascular diseases were also different between genders (Wang et al, 2015;Zhong et al, 2017). A recent study had reported that the association between the increased hypertension severity and the onset of ischemic stroke was almost twice as strong in women as in men (Madsen et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the average concentration of Hcy was 10.2 (8.3–12.8) μmol/L, and males were much higher than females. In addition, smoking can indirectly lead to the reduction or lack of folic acid and vitamin B12 levels in the blood and affect the decomposition and metabolism of Hcy [ 15 ]. This may also be the reason why the level of Hcy in men is higher than that in women.…”
Section: Discussionmentioning
confidence: 99%